KUALITAS HIDUP PASIEN KANKER PAYUDARA BERDASARKAN KARAKTERISTIK PASIEN DAN DUKUNGAN KELUARGA - Rahmiwati Rahmiwati; Yenni Yenni; Maratul Adzkiya (HUMAN CARE JOURNAL, 2022)
Breast cancer is the highest deadly disease that occurs in women. This study aimed to determine The Correlation between Patient Characteristics and Family Support Toward Breast Cancer Patients Quality of Life at RSUD Pasaman Barat. The type of this research was descriptive analytic with a cross sectional. It was conducted on July 2021 with the population was breast cancer patients recorded throughout February 2021 with 30 people. By using accidental sampling, 30 respondents were chosen as the samples with The data were collected through a questionnaire and it was analyzed by with chi-square test. The results showed that 73.3% of respondents less than 45 years, 80% had low education, 76.7% with a diagnosis less than2 years, 63.3% had undergone more than 1 type of treatment, 53.3% had support good family and 60% were in moderate quality of life. Variables related to the quality of life of breast cancer patients were age (p = 0.013), type of treatment (p = 0.006) and family support (p = 0.046). While the variables of education and duration of diagnosis were not related to the quality of life of breast cancer patients. It was concluded that age, type of treatment and family support were variables related to the quality of life of breast cancer patients.Keywords         : Family Support, Breast Cancer, Characteristics, Quality of Life